Statin prescription in patients with chronic obstructive pulmonary disease and risk of exacerbations: a retrospective cohort study in the Clinical Practice Research Datalink - Smith, MC; Ashdown, H; Sheppard, J; Butler, C; Bankhead, C (BMJ Publishing Group, 2021)
Objective Observational studies have suggested a beneficial effect of taking statins on frequency of chronic obstructive pulmonary disease (COPD) exacerbations. However, clinical trials of statins in people with COPD did not confirm those results. This study aimed to investigate this association using a methodological approach, which reduces the biases associated with some previous observational study designs. Design Retrospective cohort study comparing new-users of statins with non-users. Setting General practices in England contributing to the Clinical Practice Research Datalink in 2007–2017, with linkage to data on Hospital Episode Statistics inpatient episodes. Participants 48 124 people with COPD, aged over 40 years, who had not been prescribed statin in the previous year. Exposure Participants became new-users of statins at their first prescription for a statin during follow-up. They were then assumed to remain statin users. Statin users were compared with non-users. Outcomes Primary outcomes were COPD exacerbation, or severe exacerbation requiring hospitalisation. Secondary outcomes were death from any cause (for comparison with other studies) and urinary tract infection (negative-control). Maximum follow-up was 3 years. Adjusted HR were calculated using time-dependent Cox regression. The Andersen-Gill model was used for recurrent exacerbations. Covariates included demographic variables, variables related to COPD severity, cardiovascular comorbidities as time-dependent variables, and other comorbidities at baseline. Results 7266 participants became new-users of statins over an average 2.5 years of follow-up. In total, 30 961 people developed an exacerbation, 8110 severe exacerbation, 3650 urinary tract infection and 5355 died. Adjusted HR (95% CI) in statin users compared with non-users were first exacerbation 1.01 (0.96–1.06), severe exacerbation 0.92 (0.84–0.99), number of exacerbations 1.00 (0.97–1.04), urinary tract infection 1.10 (0.98–1.23) and death 0.63 (0.57–0.70). Conclusions In this study of health records from a Primary Care database, statin use in people with COPD was not associated with a lower risk of COPD exacerbation.